A Mutation in the CASQ1 Gene Causes a Vacuolar Myopathy with Accumulation of Sarcoplasmic Reticulum Protein Aggregates. Issue 10 (10th September 2014) - Rossi, Daniela; Vezzani, Bianca; Galli, Lucia; Paolini, Cecilia; Toniolo, Luana; Pierantozzi, Enrico; Spinozzi, Simone; Barone, Virginia; Pegoraro, Elena; Bello, Luca; Cenacchi, Giovanna; Vattemi, Gaetano; et al.
<x xml:space="preserve">Abstract</x> Calsequestrin‐1 (CASQ1) is the major Ca2+ binding protein of the sarcoplasmic reticulum (SR) of skeletal muscles. We report the first mutation in the CASQ1 gene in patients with a skeletal myopathy, characterized by muscle weakness, fatigue and the presence of aggregates of SR proteins. The CASQ1 c.731A>G (p.Asp244Gly) mutation is located in one of the high affinity Ca2+ binding sites in CASQ1 and causes the formation of protein aggregates, resulting in altered Ca2+ release in skeletal muscle fibers of patients. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>